Market power, efficiency and welfare performance of banks: evidence from the Ghanaian banking industry - David Adeabah; Charles Andoh (ZBW – Leibniz Information Centre for Economics, 2019)
The study analyses the welfare performance of banks' lending services in the Ghanaian banking industry with emphasis on the role of market power and efficiency. We made use of pooled OLS regression with fixed effect model. For robustness, we adopted Prais–Winsten (1954) regression and two-stage least squares (2SLS) instrumental variables procedures on an unbalanced panel data of 24 banks for years 2009 through 2017. The results reveal that during our study period, there was a welfare loss of about 0.433 percent of observed total loans. Encouragingly, cost efficiency in the banking system fits well within the world's mean efficiency but has been decreasing over time. Further, there is evidence that prices have not moved toward a competitive level. Cost efficiency estimates are found to be negatively associated with loss of consumer surplus estimates. Market power is found to be positively related to a loss in consumer surplus. Additional analysis shows that the market power effect is dominant in both domestic and large banks. Overall, the results indicate that market power and bank efficiency are competing interests for policymakers in their consideration of policy reforms geared toward an efficient and well-functioning banking system. An additional implication of these results suggests that antitrust enforcement may be socially beneficial to provide an incentive for competitive pricing in the lending business segment of banking. Other implications are also discussed.
Keywords: D12; D18; D60; G21; 330; Welfare Performance; Bank Efficiency; Market Power; Data Envelopment Analysis; Ghana